Penerapan Sistem Informasi Geografis pada Pemetaan Coffee Shop Daerah Jakarta Selatan Berbasis Web - Noveandini, Rahayu; Wulandari, Maria Sri; Ramzy, Naufal Aly (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The application of Geographic Information Systems (GIS) for mapping coffee shops in South Jakarta is highly relevant and beneficial. GIS allows the public to easily access more complete and accurate information about the distribution of coffee shops in the area. The problem is that there is currently no system that provides information and locations of coffee shops in South Jakarta for the general public. The development of the South Jakarta coffee shop GIS was carried out to respond to the community's need for more complete and structured location information. This web-based system makes it easier for users to find coffee shops that suit consumer needs through clear and informative spatial data visualization. This system also provides an interactive map that displays the locations of all coffee shops in South Jakarta, equipped with more detailed additional information than conventional map services, making it easier for users to search and determine the appropriate choice. The objective of this research is to develop GIS software that maps the locations of coffee shops. Leaflet.js software is used to map coffee shop locations using the Waterfall approach as the system development method. The process sequence begins with Analysis, Design, Coding, Testing, Implementation, and Maintenance, with testing using the blackbox method, and the results show that all system features function properly. System performance testing was conducted using two browsers, Chrome and Microsoft Edge, with page access speeds of 0.16 seconds for Chrome and 0.91 seconds for Microsoft Edge. For further development of the system, features such as user reviews, ratings, and recommendations based on user preferences can be added to make the system more interactive and informative.